Peculiarities of Dermatoglyphics in Minors with Suicidal Behavior - Shamsiyev, Abdulla; Abidov, Khasankhodja; Ruziev, Sherzod (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the data from theirresecurveh on the study of the peculiarities of dermatoglyphics in minors with suicidal behaviour. The authors analyzed the data of fingerprints of 26 persons who died (according to the investigation data) from suicides. The structure of the scallop skin of the suicides was studied in depth. When calculating the comb papillaries of fingers, the study was conducted on the basis of the developed software product "Analysis of combing palms, fingers and soles papillaries by the method of Iskandarov-Kuziev". Preliminary analysis of the distribution of victims by sex showed that the majority of those killed by suicide were male.